Motivation and the Foreign Language In Greek State Primary School Context - Kanela Kyriakoulia (Research Papers in Language Teaching and Learning, 2010)
The first step towards the acquisition of a foreign language is largely determined by the motivational factors present in the classroom, both with regard to the learner and with regard to the teacher. However, there are motivational factors that extend beyond classroom boundaries. The learner group, the parents and the philosophy of the school itself are three of these external factors. The aim of this small-scale research was to confirm the assumption that these three factors can heavily influence the motivation of students attending foreign language classes in the context of a State Primary School in Greece. The theoretical background supporting this assumption is considered in our presentation. Moreover, the data deriving from questionnaires distributed to learners, parents and the teaching staff reveal the extent of the influence that these three groups exercise on learners’ motivation and on the increase of their interest in the foreign language.